IMPACT OF PREVOUS ABORTUS ON FETAL WEIGHT IN PALEMBANG CITY, INDONESIA - Ismah, Zata; Tjekyan, Suryadi; Novrikasari, .; Mariana, .; Diora, Agita (LIFE: International Journal of Health and Life-Sciences, 2018)
Mothers with a history of abortion may have a risk of comorbidities during pregnancy, thus becoming one of the contributing factors of adverse pregnancy. The fetus that has experienced growth restriction will be low fetal weight. This study is using a crossectional design and it used 752 samples in 25 health services. Samples required inclusion criteria was age of pregnancy above or equal to 24 weeks. An exclusion criterion has HIV / AIDS diseases. Our results found that there was a significant association between the histories of abortion with incidence of low fetal weight. The prevalence of aborted women experienced a low of fetal weight is at 4,323 (P Value 0.001; 95% CI 2.028-9.216) greater than those never aborted. The odds of low fetal weight in pervious aborts’ mothers were 20%.